1978
DOI: 10.1007/bf00007992
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variation of phytoplankton in Loch Lomond

Abstract: A study of diurnal variation over a 48 hour period was undertaken in July 1973 to ascertain the extent and timing of some major chemical, physical and biological variables in Loch Lomond . The phytoplankton population was dominated by the diatom Tabellaria jenestrata, with a maximum abundance between 04 .00 and o6.0o h in surface waters on both days . A distinct diurnal variation in cell numbers was also recorded . Chlorophyll a values also showed a regular pattern of variation with a single peak between ,o .o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Hourly variations of chlorophyll‐a concentration observed from space were obvious throughout the day in all the ROIs (Figure ). Maximum chlorophyll‐a concentration usually occur around noon, which was similar with the temporal pattern from Lorenzen () and Maulood et al (). Similar trends of variation between photosynthetically available radiation (PAR) and chlorophyll‐a concentration among the four ROIs indicated that the diurnal variation of chlorophyll‐a concentration might due to the ability of photosynthesis to light by phytoplankton (Figures and a).…”
Section: Discussionsupporting
confidence: 85%
“…Hourly variations of chlorophyll‐a concentration observed from space were obvious throughout the day in all the ROIs (Figure ). Maximum chlorophyll‐a concentration usually occur around noon, which was similar with the temporal pattern from Lorenzen () and Maulood et al (). Similar trends of variation between photosynthetically available radiation (PAR) and chlorophyll‐a concentration among the four ROIs indicated that the diurnal variation of chlorophyll‐a concentration might due to the ability of photosynthesis to light by phytoplankton (Figures and a).…”
Section: Discussionsupporting
confidence: 85%
“…Such a dynamics has been well documented for both temperate (Maulood et al 1978;Frempong 1981;Takamura and Yasuno 1984) and tropical and subtropical ecosystems (Barbosa and Padisák 2002;Melo et al 2004;Lopes et al 2005). In general, the cited studies are based on the density or biomass of major taxonomical groups, and most related diel and vertical phytoplankton distribution to: (1) mixing properties, including atelomixis (diurnal mixing restricted to the epilimnion); (2) occurrence of selfregulating populations by flagella or aerotopes; (3) occurrence of fast-growing species, which can change in abundance during a single diel cycle.…”
Section: Introductionmentioning
confidence: 94%
“…Most studies of these species may be shade plankters attaining their maximum densities in the metalimnion, hypolimnion or below the surface. However, Maulood et al (1978) reported maximum density of Mallomonas sp. at the surface during the day.…”
Section: Discussionmentioning
confidence: 96%
“…However, in the third investigation on April 10 surface density was low despite of the irradiance of the surface layer, which was much lower compared to earlier two days; maximum density clearly appeared at 2-3 m depth during the daytime. Several studies have been performed on the vertical distribution of the Mallomonas species (Nygaard 1977;Maulood et al 1978;Smol et al 1983;Arvola 1984;Eloranta 1987;Croome and Tyler 1988;Jones 1988;Hoffmann and Wille 1992). Most studies of these species may be shade plankters attaining their maximum densities in the metalimnion, hypolimnion or below the surface.…”
Section: Discussionmentioning
confidence: 99%